2017
DOI: 10.1038/s41598-017-05867-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and characterization of G-quadruplexes in Mycobacterium tuberculosis gene promoter regions

Abstract: Mycobacterium tuberculosis is the causative agent of tuberculosis (TB), one of the top 10 causes of death worldwide in 2015. The recent emergence of strains resistant to all current drugs urges the development of compounds with new mechanisms of action. G-quadruplexes are nucleic acids secondary structures that may form in G-rich regions to epigenetically regulate cellular functions. Here we implemented a computational tool to scan the presence of putative G-quadruplex forming sequences in the genome of Mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 66 publications
3
62
0
1
Order By: Relevance
“…The TP‐G4 and OX‐1T‐G4 structures that were used for investigating the G4 resolution activity of MtUvrD1 have been derived from the murine immunoglobulin switch region and Oxytricha telomeric sequences, respectively . Mycobacterium tuberculosis genome is GC rich and possesses > 10 000 potential G4 DNA forming motifs . To test whether MtUvrD1 can unwind G4 structures that are derived from the potential G4 forming sequences from the M. tuberculosis genome, we identified recA , trpD , and MFS potential G4 forming sequences using G4 analysis tool QGRS Mapper (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TP‐G4 and OX‐1T‐G4 structures that were used for investigating the G4 resolution activity of MtUvrD1 have been derived from the murine immunoglobulin switch region and Oxytricha telomeric sequences, respectively . Mycobacterium tuberculosis genome is GC rich and possesses > 10 000 potential G4 DNA forming motifs . To test whether MtUvrD1 can unwind G4 structures that are derived from the potential G4 forming sequences from the M. tuberculosis genome, we identified recA , trpD , and MFS potential G4 forming sequences using G4 analysis tool QGRS Mapper (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that Mycobacterial UvrD binds to the 3′‐overhangs, translocates in a 3′ → 5′ direction and unwinds G4 structures. Mycobacterium tuberculosis genome possesses > 10 000 potential G4 DNA forming sequences and many of these sequences are located in promoters of various genes . Previously, we have shown that PE_PGRS2, mce1R, and moeb1 gene promoter G‐rich sequences form G4 structures .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One genome per each group of aligned sequences was chosen to serve as reference sequence, possibly belonging to the manually curated RefSeq database [https://www.ncbi.nlm.nih.gov/ refseq/]. The complete list of selected reference sequences is reported in S1 Table. PQSs were searched in all multiple-aligned nucleotide sequences with an in-house developed tool, as previously described [36,52]. Briefly, a PQS was reported when at least four consecutive guanine islands (G-islands) were detected.…”
Section: Pqs Detection and Evaluation Of Conservationmentioning
confidence: 99%
“…G4 patterns were searched in all nucleotide sequences with an in-house developed tool, as previously described (Perrone et al 2017a;Perrone et al 2017b). Briefly, a G4 was reported when at least four consecutive guanine islands (G-islands) were detected.…”
Section: Methodsmentioning
confidence: 99%